Awareness of implementation on Good Agricultural Practices (GAP) among smallholder in oil palm plantation in Tangkak, Johor / Mohd Fakrul Faris Zulkaply - Zulkaply, Mohd Fakrul Faris (Faculty of Plantation and Agrotechnology, 2018)
The government of Malaysia have ambitious targets of both grow the palm oil improve environmental quality by implementing good agricultural practices. The key agents for improved the national palm oil yields and development of the industry is smallholders after the big company like Felda, Felcra, Sime Darby, IOI and others. The study was conducted to determine the awareness of implementation on Good Agricultural Practices among smallholder in oil palm plantation in Tangkak, Johor to make the smallholder produce a good quality of palm oil for their on farm production and post production process, resulting in safe and healthy food and non-food palm oil products while taking into consideration about economic, social and environmental sustainability (FAO, 2013) equivalent with the MSPO/RSPO certification. The objective of this study is to determine the relationship of training, financial and management toward implementation of Good Agricultural Practices (GAP) among smallholders and to identify the most factors that influence the implementation of Good Agricultural Practices (GAP) among smallholder in their oil palm plantations. The method of this study is using survey method such as survey, questionnaire and SPSS. Descriptive statistic will be conducted to find the mean and to show the graph about the differences between smallholder’s information. The Pearson Correlation also needs to be analyzed to see the relationship among the independent variable and dependent variable, which will show the strong relationship between them. The Multiple Regression Method in the SPSS will be conducted to see the most influence factors between independent variables and dependent variables. This study concludes that there is a high degree of management than other factor that influence the awareness of implementation of Good Agricultural Practices (GAP) among smallholder in Tangkak, Johor.